Market Power in the Czech Banking Sector - Řepková Iveta (Journal of Competitiveness, 2012)
This paper estimates the market power in the Czech banking sector during the period 2000 2010. In order to measure the degree of market power in the Czech banking sector, the authors used the Lerner index, the Herfindahl-Hirschman index and the concentration ratio. The Lerner index is applied to data from 15 banks, which covers about 90% of the Czech banking market. The paper describes the theoretical framework of the competition, especially the Lerner index and measures of concentration. Authors also compute separate Lerner index for the Czech credit market and the Czech deposit market. The estimations of the Lerner index do not confirm either monopoly or perfect competition structure in the Czech banking sector over the period analyzed. The competition decreased in the period 2000-2005 which was affected by the decrease in the price of funds and capital. However, the competition increased in the period 2005-2010, and it was influenced by the increase in the price of funds and capital. From the value obtained from the Lerner index, it was found that the lowest competition was in the deposit market.